Changes in cardiac proteome and metabolome following exposure to the PAHs retene and fluoranthene and their mixture in developing rainbow trout alevins - Eriksson Andreas N.M.; Rigaud Cyril; Rokka Anne; Skaugen Morten; Lihavainen Jenna H.; Vehniäinen Eeva-Riikka (Elsevier B.V., 2022)
Exposure to polycyclic aromatic hydrocarbons (PAHs) is known to affect developing organisms. Utilization of different omics-based technologies and approaches could therefore provide a base for the discovery of novel mechanisms of PAH induced development of toxicity. To this aim, we investigated how exposure towards two PAHs with different toxicity mechanisms: retene (an aryl hydrocarbon receptor 2 (Ahr2) agonist), and fluoranthene (a weak Ahr2 agonist and cytochrome P450 inhibitor (Cyp1a)), either alone or as a mixture, affected the cardiac proteome and metabolome in newly hatched rainbow trout alevins (Oncorhynchus mykiss). In total, we identified 65 and 82 differently expressed proteins (DEPs) across all treatments compared to control (DMSO) after 7 and 14 days of exposure. Exposure to fluoranthene altered the expression of 11 and 19 proteins, retene 29 and 23, while the mixture affected 44 and 82 DEPs by Days 7 and 14, respectively. In contrast, only 5 significantly affected metabolites were identified. Pathway over-representation analysis identified exposure-specific activation of phase II metabolic processes, which were accompanied with exposure-specific body burden profiles. The proteomic data highlights that exposure to the mixture increased oxidative stress, altered iron metabolism and impaired coagulation capacity. Additionally, depletion of several mini-chromosome maintenance components, in combination with depletion of several intermediate filaments and microtubules, among alevins exposed to the mixture, suggests compromised cellular integrity and reduced rate of mitosis, whereby affecting heart growth and development. Furthermore, the combination of proteomic and metabolomic data indicates altered energy metabolism, as per amino acid catabolism among mixture exposed alevins; plausibly compensatory mechanisms as to counteract reduced absorption and consumption of yolk. When considered as a whole, proteomic and metabolomic data, in relation to apical effects on the whole organism, provides additional insight into PAH toxicity and the effects of exposure on heart structure and molecular processes.